2019
DOI: 10.1186/s12889-019-6411-3
|View full text |Cite
|
Sign up to set email alerts
|

Early linear growth retardation: results of a prospective study of Zambian infants

Abstract: BackgroundLinear growth retardation is the most dominant nutritional problem globally. We aimed to describe linear growth trajectory among infants under 2 years of age using the WHO growth velocity standards.MethodThis was a prospective cohort study of infants enrolled at 6 weeks of age and followed up for up to 24 months in Kamwala Urban Health Centre, Lusaka, Zambia. The study was conducted between April 2013 and March 2015. Infants were enrolled if they were 6–12 weeks of age and the mother was willing to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Contrary to longitudinal research from Bangladesh, we did not find evidence of associations between stunting or wasting and odds of rotavirus diarrhoea even before adjustment for EED [8]. Risk factors for stunting are multifactorial and intergenerational, with maternal and intrauterine exposures acting as leading risk factors for growth faltering in early life and postnatal exposures such as frequent enteric infections becoming increasingly important as children get older [6,24,25]. Future research examining the association between nutritional status, EED and diarrhoeal disease should therefore utilize longitudinal follow-up that incorporates measurements of maternal and intrauterine predictors of childhood nutritional status over time.…”
Section: Discussioncontrasting
confidence: 95%
“…Contrary to longitudinal research from Bangladesh, we did not find evidence of associations between stunting or wasting and odds of rotavirus diarrhoea even before adjustment for EED [8]. Risk factors for stunting are multifactorial and intergenerational, with maternal and intrauterine exposures acting as leading risk factors for growth faltering in early life and postnatal exposures such as frequent enteric infections becoming increasingly important as children get older [6,24,25]. Future research examining the association between nutritional status, EED and diarrhoeal disease should therefore utilize longitudinal follow-up that incorporates measurements of maternal and intrauterine predictors of childhood nutritional status over time.…”
Section: Discussioncontrasting
confidence: 95%
“…During infancy, several issues cause major concerns regarding the growth of a child. These include genetic deformities, environmental hazards and nutritional factors [24]. The recruited infants in the current population-based cohort study were all apparently healthy with normal anthropometric indexes at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study has suggested that retardation in linear growth among Zambian infants is more sever at about 13 months of age. According to the authors, the suggested age is about the time which nearly all the infants have weaned off breast milk a factor which may have severely affect children's growth [24].…”
Section: Discussionmentioning
confidence: 99%
“…During infancy, several issues cause major concern regarding growth of the child. These include, genetic deformities, environment hazards and nutritional factors [19]. At birth, the recruited infants in the current population based cohort study were all apparently healthy with normal growth indexed at birth.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the suggested age is about the time which nearly all the infants have completely been weaned off breast milk. This may have severe effects on children's growth [19].…”
Section: Discussionmentioning
confidence: 99%